Penerapan Model Pembelajaran Inkuiri Terbimbing untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SDI Lasiana melalui Penelitian Tindakan Kelas - Hano, Alvin Javier; Sukriono, Didik; Mardhatillah, Mardhatillah (Cetta: Jurnal Ilmu Pendidikan, 2024)
Primary school education plays an important role in developing students' critical thinking skills, which are essential for understanding lessons and dealing with everyday situations. Challenges arise from teaching methods that are less supportive of critical thinking skills, where students often memorise without deep understanding. The application of guided inquiry learning model offers an effective solution. By encouraging students to question, explore and find answers on their own, this model creates an interactive learning environment and enhances critical thinking skills. This study will evaluate the effectiveness of guided inquiry in improving critical thinking skills of grade IV students of SDI Lasiana. This study also aims to improve students' critical thinking skills in Pancasila Education class IV SDI Lasiana through the application of guided inquiry learning model. This research uses a class action research method which consists of various action cycles used. Planning, implementation, observation, and reflection are phases included in each cycle. This research was designed in two cycles of the Kemmis and McTaggart PTK model. The subjects of this study were fourth grade students of SDI Lasiana. The number of students was 17 people consisting of 7 boys and 10 girls. The results showed that (1) The application of the guided inquiry learning model can improve students' critical thinking skills in class IV Pancasila education subjects. (2) The application of the guided inquiry learning model can increase student activeness in the classroom so that they can better understand the material provided by the teacher. From the results of this study it can be concluded that the guided inquiry model can improve students' critical thinking skills in Pancasila Education subjects in class IV SDI Lasiana.